Application of data compression technique in congested networks - Kho, Lee Chin; Ngu, S.S.; Tan, Y.; Lim, A.O. (Springer, 2016)
One of the viable solutions for reducing congestion in networks is compression. Compression reduces data size and transmission time. The conventional compression techniques are mainly designed to compress data at application level of the Internet protocol suite and during network off-line condition. In this paper, a novel data compression-based congestion control (DCCC) technique in transmission control protocol is proposed. The DCCC can be divided into two stages, the congestion detection and compression. In the first stage, congestion status identification is performed. If it is predicted that the congestion may appear in a particular network, then a sender that satisfies the compression conditions will send for compression. The second stage consists of the dictionary construction and data encoding to eliminate/reduce redundancy. The numerical result shows that the proposed technique can save up to 20 % the network bandwidth when the block size of more than 16 Kbyte is used. © Springer India 2016.